Influence of Demographic Variables on Trust in the Banking Industry - Bhandari, Sita; Dhaubdhadel, Sarita Maiya; Pant, Sagar; Shah, Ram Uday (International Journal of Atharva, 2023)
Banks depend on trust. Commercial banks are vital to the economy because they help consumers save, lend, and manage their finances. This research was carried out to learn more about bank workers' faith in trust on a demographic basis. Quantitative data was collected from a sample of 111 individuals through a survey questionnaire. The survey assessed perceptions of trust in commercial banks. The analysis reveals that gender and educational level plays a role in trust and perceptions of leadership Marital status alone does not determine trust and perceptions, as individuals in both married and unmarried groups exhibited a range of opinions. Age and experience also do not influence trust. These findings provide insights into the dynamics of trust and perceptions of leadership. Still, they should be considered within the limitations of the dataset and the influence of other factors like organizational culture